(untitled) (Journal of Naval Architecture and Marine Engineering, 2011)
In the last year, the Department of Naval Architecture and Marine Engineering of Genoa University (now Department of Naval Architecture, Marine Technology and Electrical Engineering) collaborated to the design of the propulsion automation of two different naval vessels; within these projects the authors developed different ship propulsion simulators used to design and test the propulsion control schemes. In these time-domain simulators, each propulsion component is represented by a specific mathematical model, mainly based on algebraic and differential equations. One of the key aspects of the propulsion simulation is the engine dynamics. This problem in principle can be dealt with models based on thermodynamic principles, which are able to represent in detail the behaviour of many variables of interest (engine power and speed, air and gas pressures, temperatures, stresses, etc.). However, thermodynamic models are often characterized by a long computation-time and moreover their development usually requires the knowledge of specific engine information not always available. It is generally preferable to adopt simpler simulation models, for the development of which, very few kinds of information are necessary. In fact, for the rapid prototyping of control schemes, it is generally more important to model the whole plant (in a relatively coarse way) rather than the detailed model of some components. This paper deals with simple mathematical methods, able to represent the engine power or torque only, but they can be suitably applied to many types of marine engines in a straightforward way. The proposed simulation approaches derived from the authors’ experience, gained during their activity in the marine simulation field, and they are particularly suitable for a fast prototyping of the marine propulsion control systems. The validation process of these particular models, regarding a Diesel engine, a marine gas turbine and an electric motor, is illustrated based on the sea trials data and engine manufacturers’ data. Keywords: Dynamic simulation; marine engines performance; gas turbine; propulsion control. doi: http://dx.doi.org/10.3329/jname.v8i2.7366 Journal of Naval Architecture and Marine Engineering 8(2011) 129-147